Moral Formation: How is religious self-actualization at the Al-Qudsi Tulang Bawang Islamic Boarding School? - Adibussholih, Moh.; Subandi, Subandi; Jaenullah, Jaenullah; Indrianis, Yuli (CV. BImbingan Belajar Assyfa, 2023)
The administrators have tried to carry out their duties and responsibilities as educators entrusted by parents to educate and develop the morals of students so that they have noble morals. However, there are still some students who are unable to actualize religious values in their daily lives. This research describes the understanding, habituation, and impact of religious self-actualization in forming morals at Al-Qudsi Islamic Boarding School. Bone Onions. This research is field research carried out at Pondok Al-Qudsi Islamic Boarding School. Bone Onions are related to the actualization of religion in the formation of morals of students. Researchers, in collecting the data needed as a source of information, use observation, interview, and documentation techniques. The data obtained is then collected and processed so that it can be received withdrawn something conclusion . Based on the research results, it can be concluded that the character values facilitated by the school to be internalized in the students of the Al-Qudsi Tulang Bawang Islamic Boarding School are religious, honesty, responsibility, politeness, mutual respect, care for the environment and love of the homeland. The character values that have been actualized in students' daily behavior at the Al-Qudsi Tulang Bawang Islamic Boarding School are religion, honesty, responsibility, politeness, mutual respect, and environmental care.